PERAN PEMERINTAH INDONESIA DALAM MENANGANI IMIGRAN ILEGAL (STUDI KASUS: PEMERINTAH KOTA TANJUNGPINANG TAHUN 2016-2019) - Safitri, Nirwana Vega; Yealta, Den (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The number of illegal immigrants in Indonesia continues to increase from year to year. In 2019, UNHCR Indonesia has recorded as many as 13,900 illegal immigrants registered as asylum seekers. Tanjungpinang City is one of the areas targeted for the entry of illegal immigrants because the busy Riau Islands sea route is used for international trade flows. Therefore, this study will examine the role of the Tanjungpinang City government towards illegal immigrants in 2016-2019.This study used qualitative research methods. Sources come from books, journals, official documents and official websites from the Ministry of Foreign Affairs, the Directorate General of Immigration, and the Immigration Detention Center as well as interviews with related agencies. This study uses a pluralist perspective with the level of analysis of the state and nation. The theory used is the role theory of K.J Holsti.This study explains how the role of the Tanjungpinang City government in dealing with illegal immigrants in their area in 2016-2019. In carrying out government affairs with the principle of regional autonomy, the Tanjungpinang City Government forms a Pora Team and coordinates with relevant agencies in the field of supervision and temporary shelter as well as the security of illegal immigrants.Keywords: Government Role, Indonesian Policy, illegal immigrant, Asylum Seeker.